Vasopressin in septic shock: an individual patient data meta-analysis of randomised controlled trials - Nagendran,M; Russell,JA; Brett,S; Perkins,GD; Hajjar,L; Mason,AJ; Ashby,D; Gordon,A (Intensive Care Medicine, 2019)
PurposeWe performed an individual patient data meta-analysis to investigate the possible benefits and harms of vasopressin therapy in adults with septic shock both overall and in pre-defined subgroups.MethodsOur pre-specified study protocol is published on PROSPERO, CRD42017071698. We identified randomised clinical trials up to January 2019 investigating vasopressin therapy versus any other vasoactive comparator in adults with septic shock. Individual patient data from each trial were compiled. Conventional two-stage meta-analyses were performed as well as one-stage regression models with single treatment covariate interactions for subgroup analyses.ResultsFour trials were included with a total of 1453 patients. For the primary outcomes, there was no effect of vasopressin on 28-day mortality [relative risk (RR) 0.98, 95% CI 0.86–1.12] or serious adverse events (RR 1.02, 95% CI 0.82–1.26). Vasopressin led to more digital ischaemia [absolute risk difference (ARD) 1.7%, 95% CI 0.3%–3.2%] but fewer arrhythmias (ARD − 2.8%, 95% CI − 0.2% to − 5.3%). Mesenteric ischaemia and acute coronary syndrome events were similar between groups. Vasopressin reduced the requirement for renal replacement therapy (RRT) (RR 0.86, 95% CI 0.74–0.99), but this finding was not robust to sensitivity analyses. There were no statistically significant interactions in the pre-defined subgroups (baseline kidney injury severity, baseline lactate, baseline norepinephrine requirement and time to study inclusion).ConclusionsVasopressin therapy in septic shock had no effect on 28-day mortality although the confidence intervals are wide. It appears safe but with a different side effect profile from norepinephrine. The finding on reduced RRT should be interpreted cautiously. Future trials should focus on long-term outcomes in select patient groups as well as incorporating cost effectiveness analyses regarding possible reduced RRT use.